Investigating inflation dynamics in Indonesia: Identifying the inflation spillover for enhancing regional inflation control - Purwa, Taly; Dariwardani, Ni Made Inna; Cendekia, Diyang Gita (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
This study employs a hybrid New Keynesian Phillips curve (NKPC) model, comprising the dynamic panel, spatial dynamic panel, and semiparametric spatial dynamic panel models, to examine the dynamics of regional inflation in Indonesia from Q1 1997 to Q2 2023. The latter model, which employed the inverse distance weight (IDW), was identified as the most optimal model. The findings indicated that the lagged inflation and output gap variables transmitted a notable impact on regional inflation of Indonesia. Furthermore, the significance of the spatial spillover parameters indicates the existence of spatial regional inflation spillover in Indonesia. Jakarta, Central Java, and East Java represent the three most significant focal points of inflation dynamics in Indonesia, exerting the greatest influence on other regions. While, South Kalimantan, Jakarta, and East Java were the top three regions experiencing the greatest impact from inflationary pressures originating elsewhere. Through sensitivity analysis, it was found that a flattened Phillips curve was present throughout the period under study. It is therefore recommended that policies be intensified with a view to controlling prices, strengthening policy synergies, and improving the efficiency of goods distribution channels, both for the focal point and for regions experiencing inflationary pressures as a result of spillovers. Keywords: direct and indirect effect; inflation; non-linear model; semiparametric model; spatial spillover JEL Classification: C31; E31; F36